Investigation of the Adoption and Implementation of the e-Education Policy in the Gauteng Provincial Government - Mulaudzi, Rofhiwa (University of the Witwatersrand, Johannesburg, 2023)
Several studies have shown that school leadership plays an important role in the implementation and adoption of ICT policies in schools by creating and aligning the school vision with the policy objectives and leading change in the school. In South Africa, and Gauteng in particular, it has been found that ICT plays an important role in improving learner performance and enhancing changes in the methods of teaching and learning. It has also been evident that school leaders face different challenges during the implementation and adoption of ICT policies, such as lack of resources, bureaucracy, and resistance from the staff. The purpose of this study is therefore to investigate the adoption and implementation of the White Paper on e-Education policy in the context of teaching and learning. A qualitative approach, and in particular, the phenomenology qualitative research design, was used in this study in order to investigate the experiences of school leaders in relation to the adoption and implementation of the White Paper on e-Education within secondary schools in Gauteng province. Twenty-one school leaders were selected through convenience and purposeful non-probability sampling and requested to participate in the study. Data was collected using semi-structured interviews and analysed using the qualitative content analysis method. The following themes emerged from the study: a) participants' knowledge and understanding of the e-Education policy and application of the framework in achieving the policy goals; b) roles of participants in implementing and adopting the policy; c) school leaders’ attitude towards the policy; d) challenges faced by school leaders. The findings revealed that leaders are responsible for creating and aligning the vision of the school with policy objectives and also leading change in schools. The findings further suggested that school leaders have a common understanding of the policy and their roles in implementing and adopting it; however, they are poorly equipped for the task of implementing and adopting national policies. The study concluded by making recommendations including consideration being given to including school leadership in policy formulation processes and other stages of policy formulation and implementation in order to improve their knowledge and understanding
This research project is presented in partial fulfillment of the requirements for the degree of Master of Management by Coursework and Research Report in the WITS Graduate School of Governance at the University of Witwatersrand
Keywords: E-Education Policy; Gauteng Department of Education; Information and Communication Technologies; National Policy Development Framework; Teacher Training and Professional Development; School Leaders; SDG-4: Quality education